Respuesta :
Answer:
x= -2
Step-by-step explanation:
2(0.5× -0.6) = 0.6X
(1× -1.2) = 0.6X
-1.2=0.6X
X= -1.2/0.6
X= -2
Answer:
x=3
Step-by-step explanation:
Note: I am assuming that the “x” is a variable, and not the multiplication sign. Please correct me if I am wrong.
2(0.5x-0.6)=0.6x
Step 1: Simplify both sides of the equation.
2(0.5x)+2(-0.6)=0.6x - According to Distributive Property
x+-1.2=0.6x
x-1.2=0.6x
Step 2: Subtract 0.6x from both sides.
x-1.2-0.6x=0.6x-0.6x
0.4x-1.2=0
Step 3: Add 1.2 to both sides.
0.4x-1.2+1.2=0+1.2
0.4x=1.2
Step 4: Divide both sides by 0.4
[tex]\frac{0.4x}{0.4}=\frac{1.2}{0.4}[/tex]
x=3